Обрії слова в мовосвіті Оксани Забужко - Мовчун, Л. (Лексикографічний бюлетень, 2017)
The article deals with the analysis of the lexical and semantic component of Oksana Zabuzhko’s individual style. The social and cultural background of the era of changing epochs, which formed the linguistic personality of the writer, is considered. These circumstances have led to the widespread use of foreign language interspersed, breaking language stereotypes and intensive individual-authorial language creation. The article proves the necessity of lexicographic description and research of Oksana Zabuzhko ‘s neologisms, in particular occasionalisms, and neosemantisms.